Prevalence and molecular characterization of porcine enteric caliciviruses and first detection of porcine kobuviruses in US swine - Sisay, Zufan (2013)
The prevalence of porcine sapoviruses (SaVs) and noroviruses (NoVs) in nursing piglets on three pig farms in Ohio was studied. Fecal samples (n = 139) were collected from individual pigs and screened for caliciviruses by RT-PCR. Phylogenetic analysis was conducted using partial sequences of the RNA polymerase region. Three different SaV genogroups, including a newly emerging one (DO19 Korea-like) were detected. No NoVs were detected. Kobuviruses, emerging members of the family Picornaviridae, were detected by primers designed for SaV. To our knowledge, this is the first report of porcine DO19 Korea-like SaV and kobuvirus in the United States.